Influence analysis of the detection accuracy of atmospheric water vapor using the solar-blind ultraviolet Raman lidar. (August 2020) - Shi, Dongchen; Hua, Dengxin; Gao, Fei; Chen, Ting; Stanič, Samo
Highlights: The influence factors on the detection accuracy of atmospheric water vapor using a solar-blind ultraviolet Raman lidar are analyzed, including the O3, NO2 and SO2 absorptions, fluorescence interference, the solar background noise, optical cross talks in the polychromator system and so on. Deviations and the relative errors of water vapor retrieval due to all the predicted influencing factors are accurately estimated. To enhance the detection accuracy of the water vapor mixing ratio, the real-time measurement of O3 concentration with height is required especially in Xi'an, which can be succeeded by adding one channel to detect the vibrational Raman signal of O2 in the solar-blind ultraviolet Raman lidar. The rejection rate with more than 5 orders of magnitude to elastic scattering signal is required in the design of high resolution polychromator to avoid the optical cross talk between each extracted spectrum. Abstract: Solar-blind ultraviolet Raman lidar can realize the daytime detection of atmospheric water vapor, as the transmitting wavelength of 266.0 nm and its excited vibrational Raman spectra of N2, O2 and H2 O are within the solar-blind region. However, the spectra of the O3, NO2, SO2 absorptions and fluorescence are within the solar-blind region as well, and Raman channel of H2 O still has a small amount of residual solar background noise, which will influence the detection accuracy and detection capability of the solar-blind ultraviolet Raman lidar. Moreover, although a high efficiency polychromator is required to extract the vibrational Raman spectra of N2, O2 and H2 O, the suppression of aerosol Mie scattering and molecular Rayleigh scattering, and optical cross-talks are still required to discuss carefully in detail. Simulation results show that the retrieval accuracy of water vapor mixing ratio using the solar-blind Raman lidar are mainly influenced by the O3 absorption and the optical cross-talk of aerosol Mie scattering and molecular Rayleigh scattering. The rejection ratio with more than 5 orders of magnitude to elastic scattering signal is required in the design of polychromator to avoid the optical cross-talk between each extracted spectrum. The influences of NO2, SO2 absorptions, solar background noise and fluorescence on the retrieval of water vapor mixing ratio can be neglected. The theoretical analysis of the solar-blind ultraviolet Raman lidar on the retrieval of water vapor mixing ratio can further enhance the performance of the system detection accuracy and detection capability.